Detection of Leptospira wolffii in water and soil on livestock farms in Kelantan after a massive flood - Mohammad Sabri Abdul Rahman,; Siti Khairani Bejo,; Zunita Zakaria,; Latiffah Hassan,; Mohd Azri Roslan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Pathogenic leptospires cause leptospirosis in both animals and humans around the world. Humans can be infected by leptospires through direct contact with infected animals or indirect contact with leptospires contaminated water or soil. Outbreaks of leptospirosis usually occur after heavy rainfall and flooding, particularly in endemic areas. The aim of this study was to detect the presence of leptospires in water and soil in livestock farms after a massive flood in Kelantan. Samples were collected from 28 livestock farms in Kelantan, comprising 62 water samples and 62 soil samples, respectively. The samples were filtered and inoculated into a semisolid EMJH medium containing 5-FU for the isolation of Leptospira spp. The Leptospira spp. isolates were then identified using classical methods (1M NaCl, 8-azaguanine, and 13 °C), serology (MAT), multiplex polymerase chain reaction (mPCR), and DNA sequencing. The classical identification methods showed varying results and failed to differentiate between pathogenic and non-pathogenic leptospires. MAT showed the isolates reactions against serovars Autumnalis, Hebdomadis, Pyrogenes, Bataviae, Patoc, and Wolffii. However, mPCR showed that all isolates were non-pathogenic Leptospira spp. Further identification using DNA sequencing found that all isolates were identified as Leptospira wolffii, an intermediate species of Leptospira. The presence of L. wolffii in water and soil provides evidence that this species is circulating in the environment and could potentially transmit to humans and animals.